Bacterial communities in the solid, liquid, dorsal, and ventral epithelium fractions of yak (Bos grunniens) rumen. Issue 2 (7th November 2019) - Ren, Qingmiao; Si, Huazhe; Yan, Xiaoting; Liu, Chang; Ding, Luming; Long, Ruijun; Li, Zhipeng; Qiu, Qiang
Abstract: Yak ( Bos grunniens ) is an important and dominant livestock species in the challenging environment of the Qinghai–Tibetan Plateau. Rumen microbiota of the solid, liquid, and epithelium fractions play key roles in nutrient metabolism and contribute to host adaptation in ruminants. However, there is a little knowledge of the microbiota in these rumen fractions of yak. Therefore, we collected samples of solid, liquid, dorsal, and ventral epithelium fractions from five female yaks, then amplified bacterial 16S rRNA gene V4 regions and sequenced them using an Illumina MiSeq platform. Principal coordinates analysis detected significant differences in bacterial communities between the liquid, solid, and epithelium fractions, and between dorsal and ventral epithelium fractions. Rikenellaceae RC9, the families Lachnospiraceae and Ruminococcaceae, and Fibrobacter spp. were the abundant and enriched bacteria in solid fraction, while the genera Prevotella and Prevotellaceae UCG 003 were higher in the liquid fraction. Campylobacter spp., Comamonas spp., Desulfovibrio spp., and Solobacterium spp. were significantly higher in dorsal epithelium, while Howardella spp., Prevotellaceae UCG 001, Ruminococcaceae UCG 005, and Treponema 2 were enriched in the ventral epithelium. Comparison of predictive functional profiles among the solid, liquid, and dorsal, and ventral epithelium fractions also revealed significant differences. Microbiota in the ventral fraction of yak rumen also significantly differ from reported microbiota of cattle. In conclusion, our results improve our knowledge of the taxonomic composition and roles of yak rumen microbiota. Abstract : In this present study, we explored microbiota in the solid, liquid, and epithelium (dorsal and ventral) fractions of yak rumen, and compared functional profiles of microbiota of the four fractions, and also compared microbiota of the ventral epithelium between yak and cattle. Our results indicated the significant differences in bacterial communities between the liquid, solid, and epithelium fractions, and between dorsal and ventral epithelium fractions. Moreover, comparison of functional profiles among the solid, liquid, and dorsal and ventral epithelium fractions also revealed significant differences. Finally, we found that the microbial composition and functional profile in the ventral epithelium between yak and cattle significantly differed, suggesting the specific role of microbiota in the ventral epithelium of yak rumen.